The Hunt for the Source of Primary Interleukin-4: How We Discovered That Natural Killer T Cells and Basophils Determine T Helper Type 2 Cell Differentiation In Vivo - Yoshimoto, Tomohiro (Frontiers in Immunology, 2018)
Interleukin (IL)-4 plays a central role in determining the phenotype of naïve CD4+ T cells by promoting their differentiation into IL-4-producing T helper type 2 (Th2) cells, which are crucial for the induction of allergic inflammation. However, to date, the potential sources of ‘primary IL-4’ in vivo, as distinguished from IL-4 produced by Th2 cells, remain unclear. Here I describe the research I carried out in collaboration with Dr. William E. Paul to identify ‘primary IL-4’-producing cells and Th2 cell differentiation in vivo.